T2 mapping of molecular subtypes of WHO grade II/III gliomas - Kern, Maike (BMC Neurol, 2020)
BACKGROUND: According to the new WHO classification from 2016, molecular profiles have shown to provide reliable information about prognosis and treatment response. The purpose of our study is to evaluate the diagnostic potential of non-invasive quantitative T2 mapping in the detection of IDH1/2 mutation status in grade II-III gliomas. METHODS: Retrospective evaluation of MR examinations in 30 patients with histopathological proven WHO-grade II (n = 9) and III (n = 21) astrocytomas (18 IDH-mutated, 12 IDH-wildtype). Consensus annotation by two observers by use of ROI’s in quantitative T2-mapping sequences were performed in all patients. T2 relaxation times were measured pixelwise. RESULTS: A significant difference (p = 0,0037) between the central region of IDH-mutated tumors (356,83 ± 114,97 ms) and the IDH-wildtype (199,92 ± 53,13 ms) was found. Furthermore, relaxation times between the central region (322,62 ± 127,41 ms) and the peripheral region (211,1 ± 74,16 ms) of WHO grade II and III astrocytomas differed significantly (p = 0,0021). The central regions relaxation time of WHO-grade II (227,44 ± 80,09 ms) and III gliomas (322,62 ± 127,41 ms) did not differ significantly (p = 0,2276). The difference between the smallest and the largest T2 value (so called “range”) is significantly larger (p = 0,0017) in IDH-mutated tumors (230,89 ± 121,11 ms) than in the IDH-wildtype (96,33 ± 101,46 ms). Interobserver variability showed no significant differences. CONCLUSIONS: Quantitative evaluation of T2-mapping relaxation times shows significant differences regarding the IDH-status in WHO grade II and III gliomas adding important information regarding the new 2016 World Health Organization (WHO) Classification of tumors of the central nervous system. This to our knowledge is the first study regarding T2 mapping and the IDH1/2 status shows that the mutational status seems to be more important for the appearance on T2 images than the WHO grade.